Terrorism : perspectives from the behavioral and social sciences - Smelser, Neil J.; Mitchell, Faith (National Academy Press, 2002)
The events and aftermath of September 11, 2001, profoundly changed the course of history of the nation. They also brought the phenomenon known as terrorism to the forefront of the nation's consciousness. As it became thus focused, the limits of scientific understanding of terrorism and the capacity to develop policies to deal with it became even more evident. The objective of this report is to bring behavioral and social science perspectives to bear on the nature, determinants, and domestic responses to contemporary terrorism as a way of making theoretical and practical knowledge more adequate to the task. It also identifies areas of research priorities for the behavioral and social sciences.